Self-selection on human capital for Ukrainian refugees in Belgium - Ruxanda Berlinschi; Dieter Verhaest; Eline Poelmans; Stef Adriaenssens (Global Labor Organization (GLO), 2025)
This study documents self-selection on human capital for Ukrainian refugees. We compare the socio-demographic characteristics of a representative sample of Ukrainian refugees who registered in Belgium in the fall of 2022 with those of the Ukrainian population before the war. Contrarily to previous studies, we find negative self-selection on human capital, particularly for men and for refugees arriving from the low conflict intensity regions of Ukraine. At the same time, refugees from the low conflict intensity regions arrive with more locally-specific human capital, such as knowledge of the French language, previous visits to Belgium, and access to social networks in Belgium. Such self-selection, driven by individual incentives - economic and patriotic - has societal benefits, such as reduced brain drain for Ukraine and improved job matching in European countries offering protection.
Keywords: F22; F5; H12; 330; Russia-Ukraine war; refugees; human capital; self-selection